Learner and employer perspectives on learnership Implementation at MultiChoice - Ncube, Rugare (My University, 2021)
Youth unemployment continues to be a sticky and persistent challenge in South Africa, and while skills development initiatives are in place, the light at the end of the tunnel is still dim. Post-apartheid in 2001, the ANC led government implemented learnerships as one of the key policy instruments to address skills shortages and rising unemployment. Learnerships provide skills development through a combination of theory and practical workplace learning. This study draws on the perceptions of learners, employers and experts to understand learnership implementation at MultiChoice. The research was designed as a case study on MultiChoice and in conducting this study, qualitative research methods were deployed through the use of online interviews. Further to this document review and analysis was undertaken to further understand learnerships as well as draw insights from other studies and research on learnerships. The study is premised on the expectation that learnerships are positioned to tackle challenges of high unemployment and skills shortages. A key finding of this study is that learnerships have not been highly effective in reducing unemployment among the youth nor have they catapulted the skills required to advance careers and drive industry growth. This is due to factors such as low demand for certain skill types, limited number of jobs available and perceptions of learnerships to be inferior to university degrees. The central argument is that the high learner completion results have not been met with an equally robust job creation framework. Over and above this, the expectation placed on learnerships to address unemployment is cumbersome and to a large degree not realistic given that employability is not a function of skill only but of availability and creation of jobs. Learnerships have been effective as a skills development initiative through equipping young people with skills and experience to assist them in finding employment. There is however, opportunity to enhance the design of learnerships to improve the quality of learnership outcomes as well as repositioning the value and role of learnerships in the discourse on high unemployment
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Public and Development Management, 2021
Keywords: UCTD; Youth unemployment; Skills development; Learnerships; learnership; SDG-8: Decent work and economic growth